Activation of pheromone-sensitive olfactory neurons by plant volatiles in the moth Agrotis ipsilon does not occur at the level of the pheromone receptor protein - Vandroux, Paul; Li, Zibo; Capoduro, Rémi; François, Marie-Christine; Renou, Michel; Montagné, Nicolas; Jacquin-Joly, Emmanuelle (Frontiers in Ecology and Evolution, 2022)
In moths, mate finding relies on female-emitted sex pheromones that the males have to decipher within a complex environmental odorant background. Previous studies have shown that interactions of both sex pheromones and plant volatiles can occur in the peripheral olfactory system, and that some plant volatiles can activate the pheromone-specific detection pathway. In the noctuid moth Agrotis ipsilon, plant volatiles such as heptanal activate the receptor neurons tuned to the pheromone component (Z)7-12:OAc. However, the underlying mechanisms remain totally unknown. Following the general rule that states that one olfactory receptor neuron usually expresses only one type of receptor protein, a logic explanation would be that the receptor protein expressed in (Z)7-12:OAc-sensitive neurons recognizes both pheromone and plant volatiles. To test this hypothesis, we first annotated odorant receptor genes in the genome of A. ipsilon and we identified a candidate receptor putatively tuned to (Z)7-12:OAc, named AipsOR3. Then, we expressed it in Drosophila olfactory neurons and determined its response spectrum to a large panel of pheromone compounds and plant volatiles. Unexpectedly, the receptor protein AipsOR3 appeared to be very specific to (Z)7-12:OAc and was not activated by any of the plant volatiles tested, including heptanal. We also found that (Z)7-12:OAc responses of Drosophila neurons expressing AipsOR3 were not affected by a background of heptanal. As the Drosophila olfactory sensilla that house neurons in which AipsOR3 was expressed contain other olfactory proteins – such as odorant-binding proteins – that may influence its selectivity, we also expressed AipsOR3 in Xenopus oocytes and confirmed its specificity and the lack of activation by plant volatiles. Altogether, our results suggest that a still unknown second odorant receptor protein tuned to heptanal and other plant volatiles is expressed in the (Z)7-12:OAc-sensitive neurons of A. ipsilon.